Long-term clinical and radiological outcome of endovascular embolization of pancreatitis-related pseudoaneurysms. (March 2017) - Vander Mijnsbrugge, Ward; Laleman, Wim; Van Steenbergen, Werner; Heye, Sam; Verslype, Chris; Maleux, Geert
Background: Long-term outcome after embolization of pancreatitis-induced pseudoaneurysm is not yet determined. Purpose: To assess the long-term efficacy and patients' overall survival after embolization of pancreatitis-induced pseudoaneurysm. Material and Methods: Patients referred for endovascular treatment of a pancreatitis-induced pseudoaneurysm between January 1998 and January 2014 were analyzed. Embolization procedures were performed by transcatheter techniques using different types of embolic agents. Demographic, technical-radiological, and clinical data were collected. Results: Thirty-four patients were identified with a pancreatitis-induced pseudoaneurysm; the underlying disease was acute (n = 13; 38%) or chronic (n = 21; 62%) pancreatitis; seven patients (20.6%) had active bleeding when embolized, while in the remaining 27 patients (79.4%) the pseudoaneurysm was not bleeding. In all 34 patients, successful endovascular exclusion of the pseudoaneurysm was obtained after the first attempt. Minor complications occurred in 11 patients (30%); no major complications were noted. A new pseudoaneurysm on a different vessel was identified during follow-up in three patients (9%). In another patient (3%), the excluded pseudoaneurysm reopened during follow-up. All four recurrences occurred within the first 5 months after embolization. Long-term follow-up (mean, 6.6 years; range, 4 months–16 years) revealed estimated survival rates of 94%, 89%, and 75% after 2, 5, and 10 years respectively, without pseudoaneurysm-related death. Conclusion: Catheter-directed embolization of pancreatitis-induced pseudoaneurysms is relatively safe and effective. Recurrence or new pseudoaneurysm formation was low and occurred within the first 6 months after embolization. Overall survival is high, with no pseudoaneurysm-related deaths.